Energy Efficiency for Sustainable Development : Scale Up Strategy and Action Plan - World Bank (Washington, DC, 2013)
This study describes the Energy Efficiency for Sustainable Development (EEfSD) action plan, to scale up energy efficiency operations in client countries. The EEfSD strategy comprises of interventions at three levels: policy and regulatory, sector and sub-sector, and at end-use equipment and appliances. It is structured along four tracks: integrating energy efficiency within economic and sector work; mainstreaming energy efficiency in investment operations; improving internal operational, learning and analytic capacity; and monitoring, evaluation, and outreach. Priority focus is on countries with highest energy intensities, where rapid growth of the energy sector is expected and where total energy use is greatest. Implementation of the action plan will be guided by the Energy, Transport and Water Department, and will require cooperation and collaboration across the Bank Group, in particular the regional operations units. This paper presents the estimated incremental costs for FY07-09 which have been committed from energy trust funds and Bank budget.